Wiskott‐Aldrich syndrome protein: Emerging mechanisms in immunity. Issue 11 (12th September 2017) - Rivers, Elizabeth; Thrasher, Adrian J.
Abstract: The Wiskott–Aldrich syndrome protein (WASP) participates in innate and adaptive immunity through regulation of actin cytoskeleton‐dependent cellular processes, including immune synapse formation, cell signaling, migration and cytokine release. There is also emerging evidence for a direct role in nuclear transcription programmes uncoupled from actin polymerization. A deeper understanding of some of the more complex features of Wiskott Aldrich syndrome (WAS) itself, such as the associated autoimmunity and inflammation, has come from identification of defects in the number and function of anti‐inflammatory myeloid cells and regulatory T and B cells, as well as defects in positive and negative B‐cell selection. In this review we outline the cellular defects that have been characterized in both human WAS patients and murine models of the disease. We will emphasize in particular recent discoveries that provide a mechanistic insight into disease pathology, including lymphoid and myeloid cell homeostasis, immune synapse assembly and immune cell signaling. Abstract : WASP is an important regulator of the actin cytoskeleton with roles in immune cell functions such as cell migration, immune synapse assembly, phagocytosis and cytokine release. Cytoskeleton‐independent roles in nuclear transcription are also described. Review of WASP research in human and murine models provides valuable insight into WAS disease pathology. F‐actin, filamentous actin; WAS, Wiskott Aldrich syndrome; WASP, Wiskott Aldrich syndrome protein